Strategic Development of Community-Based Geotourism in the Tigaras Geopark Area, North Sumatra, Indonesia - Bejo Mulyadi; Dina Rosari; Suci Tiara Amirah (PT. Global Research Collaboration, 2026)
This study aims to formulate and prioritize strategic alternatives for community-based geotourism development in the Tigaras Geopark area, North Sumatra, Indonesia. Although the area has considerable scenic and geological value as part of the Toba Caldera Geopark corridor, its tourism development remains constrained by limited accommodation, sanitation, digital promotion, and stakeholder coordination. Using a sequential descriptive-analytic design that combines secondary document analysis with expert judgment, this research applies an integrated SWOT-AHP-QSPM framework to identify strategic factors and prioritize development alternatives. The results show that internal factors dominate the strategic position, with strengths and weaknesses reaching a combined weight of 0.574, while opportunities and threats reach 0.426. The normalized IFAS and EFAS scores (2.86 and 2.89) position Tigaras in a growth-oriented SO quadrant. The highest-ranked QSPM priority is the SO strategy, namely improving road access, digital infrastructure, and destination promotion (TAS = 1.28). The WO strategy, focused on strengthening community-based tourism governance, ranks second (TAS = 1.08). Within the Tigaras case, these findings indicate that sustainable geotourism development requires infrastructure modernization, digital transformation, community capacity-building, and environmental protection.